Entre el Renacimiento y el Nuevo Mundo : vida y obras de Hernán Pérez de Oliva (¿1494?-1531) - Pellús Pérez, Elena (Parecos y australes ;, 2015)
Hernán Pérez de Oliva (1494?-1531) is one of the great unknowns of the Spanish Renaissance. This book reconstructs his life and analyzes the ideological system underlying his output, showing, from a literary perspective, relations between the works -- coinciding with humanist concerns -- for better understanding his contribution to the literature on the recently discovered America for Europe.